Characteristics of Women's Gambling - Milošević, Slađana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2021)
The aim of this paper is to consider the results of research on the characteristics of women's gambling and to explain the gender differences in gambling. Gambling today is a ubiquitous multidimensional social phenomenon involving an increasing number of populations. Precisely because of the impact on the overall rate of braking problems in the general population and, more importantly, on certain risk groups in the population, first of all young people, adults, both men and women, cause great concern. Despite an estimate that one-third of gamblers are women, most of the gambling literature focuses mainly on men's gambling behavior and attitudes. Comparative analyzes between men and women show differences in the characteristics of women, such as: demographic sensitivity, progression of addiction, motivation and choice of gambling activities. Women often postpone seeking professional help due to shame and fear of stigmatization. A better understanding of gender differences in women is necessary to define effective prevention strategies and implement gender-sensitive treatment programs.